1996
DOI: 10.1159/000244281
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Growth Hormone in Perinatal Asphyxia

Abstract: To assess the pituitary response to perinatal asphyxia, the prolactin (PRL) and growth hormone (hGH) serum concentrations were measured in 55 asphyctic (15 preterm and 40 full-term) and 35 control (15 preterm and 20 full-term) newborns at 2-4,24,48 and 96 h of life. At 2-4 h the median PRL in the preterm asphyctic neonates was 5.2 U/l, whereas in the preterm control newborns it was 3.2. In the full-term newborns with and without hypoxic-ischaemic encephalopathy (HIE) it was 5.8 and 3.4, respectively. In the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…1,500 g has not been investigated. Our study shows that values of TSH, T4, and PRL in newborns treated with dopamine infusion are signifi cantly lower than those obtained in newborns of control group and than the normal values reported in literature [19][20][21] . Because, the present study was non-randomized, we cannot exclude the possibility that any effects, which are now attributed to dopamine, may also be, at least partly, due to the clinical conditions that prompted the use of dopamine.…”
Section: Discussioncontrasting
confidence: 74%
“…1,500 g has not been investigated. Our study shows that values of TSH, T4, and PRL in newborns treated with dopamine infusion are signifi cantly lower than those obtained in newborns of control group and than the normal values reported in literature [19][20][21] . Because, the present study was non-randomized, we cannot exclude the possibility that any effects, which are now attributed to dopamine, may also be, at least partly, due to the clinical conditions that prompted the use of dopamine.…”
Section: Discussioncontrasting
confidence: 74%
“…Varvarigou et al [27] measured the GH levels of healthy and asphyxiated babies and found higher GH levels in the asphyxiated infants. But the lowest concentrations were in the group with severe HIE.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PRL levels appear higher in infants born from vaginal delivery after labor and also from emergency cesarean section performed during labor than in infants delivered by elective cesarean section, indicating stimulation of fetal hypothalamic-pituitary axis during labor [222]. Significantly elevated PRL levels were also observed in neonates who experienced hypoxic-ischemic encephalopathy with seizures [223,225,226]. Moreover, basing on biochemical studies in animal models, PRL was recently hypothesized to play a considerable role in late fetal maturation and neonatal adaptation to extrauterine life, with particular concern in energetic-metabolic balance [227][228][229].…”
Section: A Physiology Of Prl In Neonates and Vlbw Infantsmentioning
confidence: 95%
“…PRL can be considered a mediator of the stress response [222][223][224] as it was observed to rise in neonates undergoing different stressful insults. In fact, PRL levels appear higher in infants born from vaginal delivery after labor and also from emergency cesarean section performed during labor than in infants delivered by elective cesarean section, indicating stimulation of fetal hypothalamic-pituitary axis during labor [222].…”
Section: A Physiology Of Prl In Neonates and Vlbw Infantsmentioning
confidence: 99%